2002
DOI: 10.1002/jcp.10095
|View full text |Cite
|
Sign up to set email alerts
|

New human myelodysplastic cell line, TER‐3: G‐CSF specific downregulation of Ca2+/calmodulin‐dependent protein kinase IV

Abstract: We have established a new hematopoietic cell line from a patient with myelodysplastic syndrome (MDS), which was refractory anemia with excess blasts (RAEB). This cell line, designated TER-3, depends on several cytokines for long-term survival and growth, and requires interleukin-3 (IL-3) for continuous growth. Cytochemical analysis revealed that TER-3 cells are weakly dianisidine positive and nonspecific esterase positive, but peroxidase negative. The surface marker profile shows that the TER-3 cells are stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Alterations of the TPs described herein are detected in solid and hematologic tumors (Table 1) (Ueno et al, 1997;Afzal et al, 1998;Harada et al, 1998;Kitagawa et al, 1998;Curran and Murray, 1999;Ellerbrock and Stack, 1999;Ishigaki et al, 1999;Brinckerhoff et al, 2000;Ellenrieder et al, 2000;Neal et al, 2000;Antczak et al, 2001a, b;Fillmore et al, 2001;Kerkela et al, 2001;Soderstrom et al, 2001;Hashida et al, 2002;Mishima et al, 2002;Seiki and Yana, 2003). In some cases, malignancy is associated with a marked increase in TP expression, whereas in others it is associated with downregulation.…”
Section: Cancermentioning
confidence: 79%
See 2 more Smart Citations
“…Alterations of the TPs described herein are detected in solid and hematologic tumors (Table 1) (Ueno et al, 1997;Afzal et al, 1998;Harada et al, 1998;Kitagawa et al, 1998;Curran and Murray, 1999;Ellerbrock and Stack, 1999;Ishigaki et al, 1999;Brinckerhoff et al, 2000;Ellenrieder et al, 2000;Neal et al, 2000;Antczak et al, 2001a, b;Fillmore et al, 2001;Kerkela et al, 2001;Soderstrom et al, 2001;Hashida et al, 2002;Mishima et al, 2002;Seiki and Yana, 2003). In some cases, malignancy is associated with a marked increase in TP expression, whereas in others it is associated with downregulation.…”
Section: Cancermentioning
confidence: 79%
“…Various studies indicate that the interaction of MTl-MMP, APN, DPPIV and ACE with their inhibitors or specific antibodies arrests cell proliferation of various cell types in vitro (keratinocytes, epithelial, endothelial and leukocytes) (Comte et al, 1997;Antczak et al, 2001a, b;Lohn et al, 2002;Mishima et al, 2002;Yoshiji et al, 2002a) and tumor xenografts (Pasqualini et al, 2000). Moreover, abrogation of TACE by oligosense nucleotide strategy or inhibition of its activity is associated with inhibition of embryonic mouse lung morphogenesis in culture (Zhao et al, 2001).…”
Section: Tps Regulate Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our assay, tumor cell lines were selected according to their expression of MMP-2 and APN, and, the concentrations inducing a 50% inhibition of cell growth (IC 50 ) in mM are reported. Among these three cell lines, HL-60 (myelo-monocytic human acute granulocytic leukemia cells having high basal APN activity) 25 and K562 cells (human chronic myelogenous leukemic cells expressing low levels of APN) 26 were selected to verify the APN inhibitory activities of target compounds, while SKOV3 cells (human ovarian carcinoma cells expressing high levels of MMP-2) 27 was selected to investigate the MMP-2 inhibitory activity. The results indicated that the anti-proliferative effects of these two compounds (A3 and A10) against HL-60 and K562 cells (data were not given) were significantly lower than the positive control.…”
Section: Structure-activity Relationship (Sars) Studiesmentioning
confidence: 99%
“…ZPP is a specific element to evaluate if employees are at increased risk for material impairment to their heme synthesis (Distelharst 1988). DNA fragmentation is a sensitive and specific aspect to evaluate whether employees are at risk of oligonucleosome impairment to the appropriate regulation of cell functions (Bonfoco et al 1995, Uwai et al 2000, Mishima et al 2002. In this study, the blood MDA, ZPP and DNA fragment levels of optoelectronic workers were determined in an attempt to be established whether occupational exposure to Ga, in and as may disrupt a normal heme production and DNA synthesis by initiating the release of lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%